2014
DOI: 10.1111/add.12668
|View full text |Cite
|
Sign up to set email alerts
|

Neurofunctional changes in adolescent cannabis users with and without bipolar disorder

Abstract: Bipolar adolescents with comorbid cannabis use do not exhibit the same over-activation of the regions involved in emotional processing as seen in adolescents with bipolar disorder alone. The absence of these findings in patients with comorbid bipolar and cannabis use disorders suggests that these individuals may have a unique endophenotype of bipolar disorder or that cannabis use may alter brain activation uniquely in bipolar disorder patients who use cannabis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…In previous studies examining adolescents who predominantly had no history of psychopathology, associations between amygdala volumes with prospective alcohol/cannabis use were also not detected (Cheetham et al, 2012(Cheetham et al, , 2014. This suggests that previous observations of amygdala abnormalities as observed in adolescents/young adults without BD but with cannabis (Gilman et al, 2014;Padula et al, 2015) or alcohol use (Dager et al, 2013) as well as in adolescents with BD and comorbid cannabis use (Bitter et al, 2014) may be related to substance exposure. Additionally, altered amygdala morphology and function in association with substance use has shown genetic and sex-related associations (Hill et al, 2001(Hill et al, , 2013Benegal et al, 2007;McQueeny et al, 2011;Cacciaglia et al, 2013).…”
Section: Neuroanatomical Factors Associated With Substance Use Problementioning
confidence: 75%
See 2 more Smart Citations
“…In previous studies examining adolescents who predominantly had no history of psychopathology, associations between amygdala volumes with prospective alcohol/cannabis use were also not detected (Cheetham et al, 2012(Cheetham et al, , 2014. This suggests that previous observations of amygdala abnormalities as observed in adolescents/young adults without BD but with cannabis (Gilman et al, 2014;Padula et al, 2015) or alcohol use (Dager et al, 2013) as well as in adolescents with BD and comorbid cannabis use (Bitter et al, 2014) may be related to substance exposure. Additionally, altered amygdala morphology and function in association with substance use has shown genetic and sex-related associations (Hill et al, 2001(Hill et al, , 2013Benegal et al, 2007;McQueeny et al, 2011;Cacciaglia et al, 2013).…”
Section: Neuroanatomical Factors Associated With Substance Use Problementioning
confidence: 75%
“…A pilot study of adolescents with BD, following subjects over 2 years, showed lower GMV in temporal cortex in those diagnosed with comorbid cannabis abuse/dependence before or after scan (n 5 7), compared with adolescents with BD without comorbid diagnoses (n 5 7) (Jarvis et al, 2008). In another study, adolescents/young adults (12-21 years) with BD and comorbid cannabis use disorders (n 5 25; 7 of whom also had comorbid alcohol abuse/dependence) were observed to have decreases in functional responses of the amygdala, shown to be excessive in adolescents with BD without comorbidity (Bitter et al, 2014). However, tobacco use was not examined in either of these studies, and GMV was not assessed in the latter study.…”
Section: Bd and Comorbid Sudsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another overlapping and limiting aspects were the high percentage of comorbid conduct disorder and cannabis use disorder in patient population. As literature suggests the strong interlink of BD with conduct disorder [58][59][60] and cannabis use disorder [61,62], thorough studies are needed in such BD population by excluding the comorbidities. A recent study reported the fluctuations in the discharge medications dosing and length of stay in adult BD population using cannabis and synthetic cannabis [63].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperactivities of the right amygdala, left nucleus accumbens, and bilateral thalamus have been reported in non-cannabis using, adolescent bipolar individuals, whereas this over-activation is reduced in BD patients who are comorbid cannabis consumers. These interesting findings raised the question of whether cannabis use alters the functionality of brain areas involved in emotional processing and reward in BD subjects or whether differences are due to the presence of unique endophenotypes (Bitter et al, 2014).…”
Section: A Functional Magnetic Resonance Imaging Studymentioning
confidence: 99%